MODEL OF INSOLATION OF THE EARTH SURFACE IN THE KARA-DAG LOCALITY ACCORDING TO SSE DATA - Volvach, A.; Kurbasova, G. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Anomalous enhancement of solar insolation of the earth’s surface in the presence of foci of excitation in its depths can cause a response at local sites. Such foci include, first of all, recent and past (retro) volcanoes, such as the ancient volcano on the territory of Kara-Dag in the Crimea. The authors of this article have found increased, in comparison with other localities of the Crimea, general insolation according to SSE. According to the 22-year linear trend, the rate of insolation growth falling on the earth’s surface at Kara-Dag has been calculated, which is 2,69 kWh/m2 per century, being more than 2 times higher than insolation growth in other areas of the Crimea. This phenomenon has been the subject of discussion, and additional research is needed, both on the geological structure of Kara-Dag and on the impact of external and internal forces. At the stage of studying the structure of data on insolation of the earth’s surface at Kara-Dag, we have built a 6-order sine-wave model. The most powerful (amplitudes more than an order of magnitude higher than the noise level) regular oscillations on the 22-year interval have periods of 365,3 and 365,7 days. Statistical estimates of the degree of approximation by a sinusoidal model (R2 = 0,9, RMSE = 0,7) indicate that, in addition to regular periodic oscillations, there are irregular fluctuations in the data at time intervals determined by a continuous time-frequency wavelet analysis. The wavelet transformation graph highlights the interval of insolation energy growth at Kara-Dag locality after 1995. In order to analyze the statistical relationship of changes in local insolation of the Earth’s surface with the Earth’s rotation around the axis and its orbital movement, solar activity and global temperature, autoregression models of the power spectral density were calculated using which coherent oscillations were found between variations in Kara-Dag paragraph and variations in the data: on the length of the day (LOD) with a period of 11,8 years and a square modulus of coherence of 0,85; about solar activity with periods of 10,5, 3,6 years and a squared coherence modulus of 0,8 and 0,85; about global temperature indices with periods of 2,3, 3,5 years and squares of coherence modulus 0,7 and 0,9, respectively.